2009
DOI: 10.1364/ol.34.000331
|View full text |Cite
|
Sign up to set email alerts
|

Impulse attack free double-random-phase encryption scheme with randomized lens-phase functions

Abstract: Security of the conventional Fourier-based double-random-phase encryption (DRPE) technique is prone to impulse attacks, as the Fourier transform (FT) of a delta function results in a unity function. To negate such an attack, the phase factors of the lenses are modified by multiplying these with random-phase functions. Owing to this modification of the FT as a result of the randomized lens phase function, a modified FT (MFTLR) gives the random output for a delta function input. Employing MFTLR in the DRPE techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(34 citation statements)
references
References 14 publications
0
34
0
Order By: Relevance
“…finding its point spread function (PSF), it will produce the decryption key at the output (20). Some recent works have addressed this major issue with encryption scheme using randomized lens-phase functions (21). Whereas most investigated optical encryption techniques have been coherent optical systems, there are very few incoherent optical techniques, which inherently have better signal-to-noise ratio (S/N) compared to its coherent counterpart.…”
Section: Introductionmentioning
confidence: 99%
“…finding its point spread function (PSF), it will produce the decryption key at the output (20). Some recent works have addressed this major issue with encryption scheme using randomized lens-phase functions (21). Whereas most investigated optical encryption techniques have been coherent optical systems, there are very few incoherent optical techniques, which inherently have better signal-to-noise ratio (S/N) compared to its coherent counterpart.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that a plurality of attacks have been designed to break DRPE systems [23][24][25][26][27][28][29][30], different approaches were suggested to improved security in DRPE. For instance, it has been demonstrated that quantum encryption systems that works with few photons are very secure [31,32].…”
Section: Encryption and Validationmentioning
confidence: 99%
“…Consequently, additional improvements with optical security techniques [16][17][18][19][20][21][22] could be adapted to be used with focused beams. To avoid conventional attacks against the information encrypted in the longitudinal component [23][24][25][26][27][28][29][30], the use of quantum imaging techniques is suggested [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Especially since the double random-phase encryption method [1] was proposed, all kinds of random-phase encoding (RPE) schemes based on diffraction or interference principles have been booming [2][3][4][5][6][7][8][9][10][11][12][13]. As the accompanying complementary opposites, the corresponding security analyses have also been carried out and have promoted the further development of optical encryption techniques [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%